Endoscopic treatment of hypertensive intracerebral hemorrhage: A technical review - Yi-ning Zhao (KeAi Communications Co., Ltd., 2016)
Hypertensive intracerebral hemorrhage (ICH) is still a highlighting global issue. Endoscopic evacuation as a minimally invasive treatment became an alternative other than conventional craniotomy and catheter drainage for ICH. However, there is no unified indication or standardized procedure on endoscopic treatment of ICH. Here we explored the literature and gathered information from different studies, to review the background, technical points, and existing problems of endoscopic treatment for ICH. Keywords: Endoscopic treatment, Hypertension, Intracerebral hemorrhage (ICH), Hematoma evacuation